2019
DOI: 10.3389/fpsyg.2019.02606
|View full text |Cite
|
Sign up to set email alerts
|

An Event-Related Potential Study of Decision-Making and Feedback Utilization in Female College Students Who Binge Drink

Abstract: This study investigated the ability to use feedback for decision-making in female college students who binge drink (BD) using the iowa gambling task (IGT) and event-related potentials (ERPs). Twenty-seven binge drinkers and 23 non-binge drinkers (non-BD) were identified based on scores on the Korean version of the Alcohol Use Disorder Test and the Alcohol Use Questionnaire. The IGT consists of four cards, including two cards that result in a net loss, with large immediate gains but greater losses in the long t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…Nineteen studies (Baker et al., 2011; Baker, Wood, et al. 2016; Bodkyn & Holroyd, 2019; Crane et al., 2021, 2023; Hammond et al., 2021; Hixson et al., 2019; Lannoy et al., 2017; Na et al., 2019; Parvaz et al., 2015; Potts et al., 2014; Sehrig et al., 2019; Singh et al., 2023; Soder et al., 2020; Wei et al., 2018, 2020, 2021; Zhao et al., 2017; Zhong et al., 2020) measured the RewP ( k = 29 effect sizes) for a total sample of N = 1089 (537 substance use, 552 control). There was no significant difference in the RewP amplitude between substance misuse and comparison groups ( g = 0.07, 95% CI [−0.44, 0.58], p = .777).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies (Baker et al., 2011; Baker, Wood, et al. 2016; Bodkyn & Holroyd, 2019; Crane et al., 2021, 2023; Hammond et al., 2021; Hixson et al., 2019; Lannoy et al., 2017; Na et al., 2019; Parvaz et al., 2015; Potts et al., 2014; Sehrig et al., 2019; Singh et al., 2023; Soder et al., 2020; Wei et al., 2018, 2020, 2021; Zhao et al., 2017; Zhong et al., 2020) measured the RewP ( k = 29 effect sizes) for a total sample of N = 1089 (537 substance use, 552 control). There was no significant difference in the RewP amplitude between substance misuse and comparison groups ( g = 0.07, 95% CI [−0.44, 0.58], p = .777).…”
Section: Resultsmentioning
confidence: 99%
“…Leave‐one‐out sensitivity analyses did not find that removing any of the 19 studies would significantly change pooled g (Table 4). However, two studies, when excluded from combinatorial meta‐analyses, were found to visibly shift the distribution of all possible effect sizes up (Na et al., 2019; Figure 4a) or down (Wei et al., 2018; Figure 4b). In both cases, excluding the outlier study removed high‐heterogeneity effect sizes, resulting in slightly lower overall heterogeneity and a flatter distribution of heterogeneity estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in their experiment, college students who were identified as stable high binge-drinkers made less advantageous choices on the gambling task than their low binge-drinking peers. In a recent study that used event-related potential (ERPs) and IGT to assess the impact of binge drinking on decision-making in female college students, Na et al (2019) found a strong correlation between binge drinking and decision-making deficits. As shown previously, alterations to brain regions that mediate the decision-making process following binge alcohol consumption offer potential explanations to the deficits in decision-making observed in these two studies.…”
Section: Effect Of Adolescent Binge Drinking On Higher Cognitive Abil...mentioning
confidence: 99%
“…Again, Moreno et al (2012) found decision-making deficits in the absence of inhibitory control impairments. Also, Na et al (2019) assessed, by means of Event-Related Potentials, the ability to use feedback for decision-making in female college students binge drinkers and found a deficit in the early evaluation of positive vs. negative feedback, concluding that this deficit may impact on dysfunctional behavioral decision-making.…”
Section: Executive and Decision-making Dysfunction In Adolescents Wit...mentioning
confidence: 99%